PERTUMBUHAN DAN PERKEMBANGAN TANAMAN PURWOCENG PADA BUDIDAYA SECARA HIDROPONIK NUTRIENT FILM TECHNIQUE (NFT) - Eni Sumarni; Loekas Soesanto; Noor Farid; Hanif Nasiatul Baroroh (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
Purwoceng sustainability is done in order to optimize its sustainable use. Therefore it is necessary to planting Purwoceng in a controlled and planned manner. Hydroponics is one of the alternative cultivation techniques for crop production without using soil, so it can be done in areas that are difficult to cultivate. Nutrient Film Technique (NFT) is one of the hydroponic techniques of water culture. The nutrients and water are administered to the plant in a circular in a shallow layer. NFT provides proper environmental control of root areas, as well as efficient water and plant nutrients. This study aims to obtain growth and development of medicinal plants Purwoceng NFT. The study was conducted from May to July 2017. The research location of Dieng Kulon at an altitude of 2.000 m asl. The Purwoceng plant was planted with NFT technique within 5 replications. The measurement results are shown in graphical. Indicators of nutritional adequacy using EC (Electrict Conductivity) and pH. EC nutrient used is 1-1.5 mS / cm for purwoceng 1-30 HST, 1.5-2 mS / cm for plants > 30 HST, pH used 5.5-6.5. The results showed that average growth of Purwoceng plants until the age of 50 HST reaches 7-9 cm. The number of branches of Purwoceng plants up to the age of 50 HST reaches 2-4 branches. The percentage of Purwoceng plants experiencing timber in the NFT system reached 40%. Therefore it is necessary to do further research how influence duration of nutrition to growth and result of Purwoceng.